1989
DOI: 10.1530/jrf.0.0870633
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary response to exogenous LHRH in superovulated women

Abstract: The response of the pituitary to exogenous LHRH was investigated in 9 normally ovulating women during the late follicular phase of a spontaneous (control) cycle, a cycle during treatment with clomiphene and a cycle during treatment with 'pure' FSH. During clomiphene treatment, basal FSH concentrations increased significantly up to Day 6 of the cycle and then decreased progressively while basal LH values showed a continuous rise. During treatment with FSH, basal LH concentrations decreased significantly. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
24

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 16 publications
6
49
0
24
Order By: Relevance
“…GnSAF is a putative ovarian factor which in superovulated women attenuates the pituitary response to exogenous LHRH (Messinis & Templeton, 1989, 1990. In the present study an attempt was made to determine whether hFF obtained from superovulated women contains GnSAF bioactivity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…GnSAF is a putative ovarian factor which in superovulated women attenuates the pituitary response to exogenous LHRH (Messinis & Templeton, 1989, 1990. In the present study an attempt was made to determine whether hFF obtained from superovulated women contains GnSAF bioactivity.…”
Section: Discussionmentioning
confidence: 96%
“…The degree of LH surge attenuation is related to the degree of ovarian hyperstimulation and it has been suggested that ovarian non-steroidal factors are responsible (Messinis et ai, 1986b; Messinis & Templeton, 1987). The pituitary response to exogenous LHRH is signifi¬ cantly attenuated, in the mid-and late follicular phases ofthe cycle, in women hyperstimulated with clomiphene citrate or 'pure' FSH (Messinis & Templeton, 1989, 1990. These studies have provided evidence that hyperstimulated ovaries produce a substance which attenuates the endogenous LH surge through the reduction of the pituitary response to LHRH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent decades, the search for putative new substances secreted by the ovaries has provided new insights into the role of the ovaries in gonadotropin secretion. This chapter focuses on the factor known as attenuin (Messinis & Templeton, 1989;Sopelak & Hodgen, 1984).…”
mentioning
confidence: 99%
“…Υπάρχουν συσσωρευµένες αποδείξεις ότι ένας µη στεροειδικός ωοθηκικός παράγων, που ονοµάζεται GnSAF, πιθανόν να εµπλέκεται στον έλεγχο της υποφυσιακής ευαισθησίας στη GnRH στις φυσιολογικές γυναίκες, ανταγωνιζόµενος την ευαισθητοποιό επίδραση της Ε2 (Messinis and Templeton, 1989;Fowler et al, 2003;Messinis, 2006). Πρόσφατα δεδοµένα παρέχουν ενδιαφέρουσες πληροφορίες όσον αφορά το χαρακτηρισµό αυτού του παράγοντα (Karligiotou et al, 2006).…”
Section: συζητησηunclassified